Knowledge on modes of HIV transmission and attitude related to working with people living with HIV among health care trainees in Malaysia - Supramaniam, Kashtoori; Mohd Ghazali, Sumarni; Kee, Chee Cheong; Lim, Kuang Hock; Ibrahim, Normala (Community Health Society Malaysia, 2016)
Background: Poor HIV knowledge and attitude among health care personnel were reported to compromise the care of people living with HIV (PLWH). This has been shown to arrest the success of HIV preventive, care and support measures in general. The objective of the study was to determine knowledge on modes of HIV transmission and attitude related to HIV among health care trainees. Materials and Methods: A total of 1404 trainees in an allied health sciences college in Malaysia consented in this cross sectional study. The data was collected using a self-administered questionnaire which consisted of knowledge on different modes of HIV transmission and attitudes related to HIV. Result: The overall response rate was 96.6% and majority of the respondents were able to identify different modes of HIV transmission namely sexual transmission (>75%), needle sharing (99.5%), blood transfusion (94.3%) and mother to child (85.8%). However, there were common misconceptions about HIV particularly with regards to HIV transmission via social contacts and other modes of transmission among. Up to 50% still have fears and discriminatory attitudes in relation to HIV. Conclusion: Health care training requires more comprehensive HIV education subject in the curricula in order to improve HIV knowledge and attitude amongst health care trainees.